Development of Android E-Modules in the Form of Flip Books Based on Balinese Local Wisdom - Wiradnyana, I Gede Arya; Pramana, Komang Agus Budhi Arya; Purandina, I Putu Yoga (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
This study aims to produce an android e-module in the form of a flip book based on Balinese local wisdom on the course of early childhood language development methods that meet the feasibility in terms of content and construct validity as well as practical use in the classroom. This is a research and development (R&D) method with the Borg & Gall model. This study collected data using interview guidelines, questionnaires, and observation sheets. The data analysis technique used is descriptive statistics. The obtained data are then examined to determine the validity and practicability of the produced product. According to the testing findings, the android e-module in the form of a Flip Book based on Balinese local knowledge has fulfilled the feasibility in terms of content validity in the very excellent category with a score of 4.63 out of a possible score of 5.00. Meanwhile, students' ratings in terms of practicality in terms of time usage, which is classed as efficient, are in the good category, totaling 3.76 out of a maximum score of 5.00. The results of this study have implications for the use of e-modules which can be used as an alternative in teaching effective, efficient, and interesting language development methods courses because they are packaged in digital form.